ETIKA BISNIS DIGITAL DALAM TRANSFORMASI UMKM : STUDI FENOMENOLOGI PELAKU USAHA MARKETPLACE - Andrianto Andrianto; Muh Nashiruddin Darajat (J-MACC, 2026)
The rapid growth of digital marketplaces has transformed the business practices of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, particularly in transaction processing and financial management. This study aims to explore how MSME actors experience, interpret, and apply business ethics and accounting ethics within digital marketplace-based business activities. Using a qualitative phenomenological approach, data were collected through in-depth semi-structured interviews and contextual observations involving MSME owners who actively utilize digital marketplaces such as Shopee, Tokopedia, and TikTok Shop. The data were analyzed using thematic phenomenological analysis based on the Colaizzi model. The findings reveal that although marketplaces provide objective and systematically recorded digital transaction data, these data are not fully integrated into MSMEs’ internal accounting systems. Accounting practices tend to be partial and situational, with frequent omissions of transaction components such as platform service fees, discounts, and sales returns, as well as the mixing of personal and business finances. These practices indicate weak internalization of accounting ethical principles, including integrity, objectivity, professional competence, and accountability. The study demonstrates that digitalization alone does not automatically foster ethical accounting behavior among MSMEs. The novelty of this research lies in its phenomenological insight into the ethical meanings constructed by MSME actors in digital accounting practices, highlighting the gap between technological transparency and ethical accountability. The study concludes that strengthening accounting ethics through digital accounting literacy, ethical education, and system integration is essential to support sustainable and accountable MSME development in the digital economy.